Pengaruh Mikoriza dan Pupuk NPKMg terhadap Pertumbuhan dan Produksi Kopi Arabika - Usman Daras; Iing Sobari; Octivia Trisilawati; Juniaty Towaha (Pusat Penelitian dan Pengembangan Perkebunan, 2015)
Mycorrhiza is a biological agent that could improve the efficiency of chemical fertilizers (inorganic) due to it can increase the availability of soil nutrients. The study aimed to evaluate the effectiveness of mycorrhiza and NPKMg fertilizers on growth and yield of coffee plants in the field. The research was carried out at KP. Pakuwon, Sukabumi, West Java, from January 2013 to November 2014. The treatments that examined in this study were 3 levels of mycorrhiza application (M0, without mycorrhizal fungi; M1, application of 200 spore/tree; and M2, application of 400 spore/tree), and 4 dosage of NPKMg fertilizers (F1, recommended dose, RD; F2, ¾ RD; F3, ½ RD, and F4, ¼ RD). The treatments were arranged in a ramdomized block design with 3 replications, and the plot size consisted of 4 coffee plants. The recommended dose of fertilizer is 140 g NPKMg/tree/years (40 g urea, 50 g SP-36, 30 g KCl, and 20 g kieserit). NPKMg fertilizers were applied two times, whereas mycorrhiza was given two months after the first application of NPKMg fertilizers. The observed parameters were vegetative characters (plant height, stem diameter, number of branch) and generative character (coffee yield) as well as the infection rates of mycorrizha on roots. The results showed that application of 400 spores of mycorrhizal fungi and 105 g NPKMg/tree/year exhibited the best growth of coffee plants until 15 months after planting (MAP). However, that combination was not significantly affected coffee production. Moreover, application of 200 and 400 spores of mycorrhizal fungi/tree combined with all dosage of NPKMg fertilizers revealed the same infection rates of mycorrizha on roots.